MAKNA SIMBOLIS DALAM NOVEL LAYAR TERKEMBANG - Hanafi Hanafi; Akhmad Baihaqi (Universitas Sultan Ageng Tirtayasa, 2021)
This study is aiming to investigate (1) the symbolic meaning of the protagonist in Sutan Takdir Alisyahbana's novel of Layar Terkembang; (2) the symbolic meaning of the title of Layar Terkembang novel; and (3) the difference between the symbolic meaning of the former Layar Terkembang novel and its current one. This study used qualitative method. The results of this study prove that the figure of Maria is a symbolic meaning of past traditional Indonesian culture; meanwhile, the figure of Tuti is a symbolic meaning of modern Indonesian culture, sophisticated to Western-style, dynamic industrialization, and high emancipation. Then, the title of Layar Terkembang is a symbol of efforts to develop intellectualism, industrialization, individuality, science and technology, and information and communication to sophisticated systems. The study also proves that the former Layar Terkembang used to be based on the spirit for Indonesian independence; now is based on the spirit to develop the country in various fields.